SPIRITUAL LEADERSHIP DAN JOB SATISFACTION (STUDI FENOMENOLOGI DI PERGURUAN TINGGI ISLAM) - Rahmatika, Arivatu Ni'mati; Al Wahidi, Akbar Fauzan; Mawardi, Imam (IAI Darussalam, 2023)
Spiritual leadership in this era is very much needed for educational institutions, especially Islamic tertiary institutions, it cannot be denied that spiritual leadership is the key to organizational change and improvement, from these educational institutions it is inseparable from the presence of lecturers as a leader to guide students to become someone who better, but there are still many lecturers who act inappropriately as leaders or leaders, therefore this research examines spiritual leadership to change the awareness of lecturers and staff employees and provide inspiration and motivation for them to achieve maximum performance voluntarily beyond the target and formal standards without being forced by leaders. The author contributes to further researching and understanding the performance of lecturers and staff at educational institutions at Kh Abdul Wahab Hasbullah University by using a qualitative methodology to obtain information by decrypting, analyzing, and further surveying an Islamic educational institution to improve the performance of an institution. The type of qualitative approach used is a qualitative approach to the phenomenological method, the subject lies mostly with lecturers and staff employees because respondents play an important role in improving the performance of an educational institution. After conducting research, researchers can conclude that the results of spiritual leadership in accordance with theories such as vision, Expectational confidence, promotion, salary, work group, there are only two theories that are not appropriate, namely the theory of altruism and supervisors. Keywords: spiritual leadership, job satisfaction, Islamic tertiary institutions Spiritual leaderhip pada era ini sangat diperlukan teruntuk di lembaga pendidikan khususnya perguruan tinggi islam, tidak dapat di pungkiri bahwa spiritual leadership menjadi kunci dalam sebuah perubahan dan perbaikan organisasi, dari lembaga pendidikan tersebut tidak lepas dengan adanya dosen sebagai seorang leader untuk membimbing mahasiswa menjadi seseorang yang lebih baik, akan tetapi masih banyak dosen yang bertindak tidak sesuai selayaknya sorang leader atau pemimpin, oleh karena itu penelitian ini mengkaji tentang kepemimpinan spiritual untuk mengubah kesadaran dosen dan staf karyawan serta mememberikan inspirasi dan motivasi mereka supaya mencapai kinerja yang maksimal secara sukarela diluar target dan standar formal tanpa dipaksa para pemimpin. Penulis berkontribusi untuk meneliti dan memahami lebih jauh kinerja dosen dan karyawan di lembaga pendidikan Universitas Kh Abdul Wahab Hasbullah dengan menggunakan metodologi kualitatif untuk memperoleh informasi dengan cara mendekripsi, menganalisis, dan mensurvei lebih lanjut suatu lembaga pendidikan Islam untuk meningkatkan kinerja suatu lembaga. Jenis pendekatan kualitatif yang digunakan adalah pendekatan kualitatif metode fenomenologi, subjek sebagian besar terletak pada dosen dan staf karyawan karena responden memegang peranan penting dalam meningkatkan kinerja suatu lembaga pendidikan. Setelah melakukan penelitian peneliti dapat meyimpulkan bahwa hasil penelitian spiritual leadership sesuai dengan teori seperti visi, Expectational confidance, promotion, salary, work group, hanya ada dua teori yang tidak sesuai yaitu teori altruisme dan supervisor. Kata kunci : spiritual leadership, job satisfaction, perguruan tinggi islam